Evaluation of Pharmaceuticals Storage in Class C Hospital Pharmacy Installation of Kebumen - Aghitska Zainin Nisa; Ranita Rahmaniar (CERATA Jurnal Ilmu Farmasi, 2025)
Storage is an important stage in the management of pharmaceuticals to ensure quality, prevent irrational use, and minimize the risk of expired and damaged pharmaceutical supplies. This study aims to evaluate pharmaceutical storage in the Class C Hospital of Kebumen based on Minister of Health Number 72 of 2016 and Minister of Health Number 5 of 2023, as well as the Department of Health and Pudjaningsih's storage indicators. This study used a cross-sectional observational design. Data were collected through observation using a questionnaire checklist, interviews with pharmacists, and assessment of storage indicators. The results of the study showed that the percentage of storage compliance has not met the standard. The results of the storage indicators, including the suitability with stock cards <100% in all pharmacy installations, the percentage of expired and damaged pharmaceutical supplies >0% in all pharmacy installations, the percentage of dead stock >0% in all pharmacy installations, and the Turn Over Ratio (TOR) at PKU Muhammadiyah Sruweng and RSUD Prembun outside the range of 8-12 times per year. The storage indicator that has met the standard is the FEFO arrangement system of 100%. Storage in Class C Hospital Pharmacy Installation Kebumen were not in accordance with standards, and an evaluation is needed to optimize storage.